Modelling the heuristic dynamics of the wage and price curve model of equilibrium unemployment - Dag Kolsrud; Ragnar Nymoen (Statistics Norway, Research Department, 2012)
A standard model of equilibrium unemployment consists of static equations for real wage ambitions (wage curve) and real wage scope (price curve), which jointly determine the NAIRU. The heuristics of the model states that unless the rate of unemployment approaches the NAIRU from any given initial value, inflation will be increasing or decreasing over time. We formalize this influential heuristic argument with the aid of a dynamic model of the wage-price spiral where the static theory's equations are re-interpretated as attractor relationships. We show that NAIRU unemployment dynamics are sufficient but not necessary for inflation stabilization, and that the dynamic wage-price spiral model generally has a dynamically stable solution for any pre-determined rate of unemployment. We also discuss a restricted version of the model that conforms to the accelerationist view that inflation increases/falls if unemployment is not at its 'natural rate'.
Keywords: E24; E30; J50; 330; AS-AD; equilibrium-correction; imperfect competition; macroeconomics; NAIRU; Phillips curve; unemployment; wage-price spiral.